Product structure initialization, the bottleneck of ERP implementation in customer driven environments: a case study - Niestanak, S. Abedi; Abdul Aziz, Faieza; Sulaiman, Shamsuddin; Mohd Yusuff, Rosnah (Universiti Putra Malaysia Press, 2011)
This study of the implementation of enterprise resource planning (ERP) in a customer driven environment analyzes the critical success factors throughout the initialization phase. The dynamic and stochastic nature of customer driven environments results in a massive workload of product structure configuration tasks related to new arrivals on one hand and a constant updating process on the other. Meanwhile, the development and implementation of an ERP system was studied from the very first step (i.e. the feasibly study for implementing an ERP) to the last step (i.e. testing the outputs of the implemented system) in an office furniture company for three years. The study involved analyzing of the data collected that were from a series of interviews, as well as direct observations and reviewing of the company's documents. Based on the output of the analysis phase, a top-down hierarchical analysis of goals and CSFs were carried out according to the CSF analysis method. Three top level objectives included reducing project failure risk, project cost, and project time. Analysing the primary results of the study (i.e. activity model, data flow diagram DFD of different levels, system problems and potential solutions descriptions, etc.) revealed that the critical phase of the implementation project would be product structure initialization and this should be taken into consideration as the bottleneck of production planning in customer driven environment, which dramatically reduced the ERP efficiency in this kind of environment. Moreover, initializing issues of the same process is the main obstacle to the success of the ERP implementation, as it considerably raises the project failure risk and cost. Therefore, the simplification, facilitation, and automation of the PSCM process, which lead to acceleration of this process, are the most significant success factors for the ERP implementation projects in customer driven environment.